PUISI ARAB DAN PROTES SOSIAL : KAJIAN STRUKTUR-MUATAN PUISI SHA'ALIK PRA-ISLAM - Andri Ilham (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
This article aims to introduce another trend in pre-Islamic Arabic poetry as opposed to tribalism. This trend is particularly as reflected in brigand poetry (Sha‘âlîk). In the content, Sha‘âlîk poems are not derived from tribal personality similarly to the poem that’s being used in tribes, however derived from an act of rebelliousness and protest against the dominating social disparities in tribes life. The goal of protest’s Sha‘âlîk was against poverty dan social disparities. So, there are two kinds of Sha‘âlîk’s poems. First, protest against differenciation of genealogical tribe. This tribe was marginalizied Arab tribe. Second, protest against poverty which caused by social disparity in the tribe life.DOI: 10.15408/a.v2i2.2126